Properties of h -convex functions related to the Hermite–Hadamard–Fejér inequalities - Bombardelli, Mea; Varošanec, Sanja (Computers & mathematics with applications (1987), 2009)
In this paper we prove the Hermite–Hadamard–Fejér inequalities for an h -convex function and we point out the results for some special classes of functions. Also, some generalization of the Hermite–Hadamard inequalities and some properties of functions H and F which are naturally joined to the h -convex function are given. Finally, applications on p -logarithmic mean and mean of the order p are obtained.